POWER-SAVING PROCEDURES AND ANIMAL THERMAL COMFORT AT A GROWING/FINISHING SWINE PRODUCTION UNIT - SARUBBI, JULIANA; ROSSI, LUIZ ANTONIO; LARANJEIRA, EVANDRO GOMES; DE OLIVEIRA, RAFAEL AUGUSTUS; VELLOSO, NINA MIGLIORANZA (Revista Brasileira de Engenharia de Biossistemas, 2008)
Climate control systems are one alternative for minimizing losses due to high temperature and large thermal variations in swine production units. However, because of the possibility of increase the productions cost, the benefits of climate control systems should be assessed before they are implemented. This research aims to assess the efficiency of different swine growing and finishing facilities regarding the animal thermal comfort, and the use of electric energy. The treatments are the following: S1 – two old automatic started fans + constructively inappropriate, S2 – two new automatic started + constructively inappropriate fans, S3 – one old manual started fan + constructively inappropriate, S4 - no one acclimatization system + constructively appropriate. The variables used in comparing these constructions were dry-bulb temperature, relative humidity, enthalpy and the thermal control index (ITH), as well as the electric variables and electric energy efficiency indexes. The use of two new fans and a sprayer system, both automatically started, provided animals with better thermal comfort, than compared wit h old ones. The use of automatic climate control equipment improves thermal comfort conditions as well as the use of electric energy.